Factors Affecting the Formation of a Positive Attitude to the Learning Activity in Students (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The article discusses the factors that influence the formation of a positive attitude to educational activities among students. Ways to achieve effective results in the educational process have been reflected on the basis of a detailed study of the factors affecting the educational activity.